Risk factors for complications of ERCP in primary sclerosing cholangitis - Ismail, S.; Kylänpää, L.; Mustonen, H.; Halttunen, J.; Lindström, O.; Jokelainen, K.; Udd, M.; Färkkilä, M. (Endoscopy, 2012)
Background and study aims: Endoscopic retrograde cholangiographic pancreatography (ERCP) is the most accurate technique for surveillance of patients with primary sclerosing cholangitis (PSC). Our aim was to evaluate risk factors for complications of ERCP in patients with PSC. Patients and methods: In 2007 – 2009 we performed 441 ERCPs in patients with PSC. The primary tools for ERCP were a guide wire and papillotomy knife to gain access into the biliary duct. If the primary cannulation failed, and the wire went only into the pancreatic duct, pancreatic sphincterotomy was performed. If necessary, a further oblique cut with a needle knife was done in order to expose the biliary duct. Results: Primary cannulation was successful in 389 patients (88.2 %). Of these, 147 (37.8 %) had had biliary sphincterotomy performed previously. In the group with failed primary cannulation, access into the biliary duct was achieved after pancreatic sphincterotomy in 52 patients. In 11 of these, a further cut with a needle knife was performed. Post-ERCP pancreatitis (PEP) was diagnosed in 31 patients (7.0 %). Factors predicting PEP were female sex (odds ratio [OR] 2.6, P = 0.015) and a guide wire in the pancreatic duct (OR 8.2, P < 0.01). Previous biliary sphincterotomy was a protective factor (OR 0.28, P = 0.02). The risk of PEP increased with the number of times the wire accidentally passed into the pancreatic duct (P < 0.001). Cholangitis developed in 6 patients (1.4 %).Conclusions: In patients with PSC the incidence of ERCP complications remained relatively low. The complication risk increased with the complexity of cannulation. In a patient with PSC in whom follow-up ERCP is planned, biliary sphincterotomy should be considered, as it may protect against PEP.